We have to solve: e^2x - 6e^x + 5 = 0

e^2x - 6e^x + 5 = 0

let e^x = t

=> t^2 - 6t + 5 = 0

=> t^2 - 5t - t + 5 = 0

=> t(t - 5) - 1( t - 5) = 0

=> (t - 1)(t - 5) = 0

=> e^x = 1 and e^x = 5

=> x = 0 and x = ln 5

**The solution of the equation is x = 0 and x = ln 5**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now